Evaluation of parallel copying garbage collection on a shared-memory multiprocessor - Imai, A.; Tick, E. (IEEE transactions on parallel and distributed systems, 1993)
A parallel copying garbage collection algorithm for symbolic languages executing on shared-memory multiprocessors is proposed. The algorithm is an extension of Baker's sequential algorithm with a novel method of heap allocation to prevent fragmentation and facilitate load distribution during garbage collection. An implementation of the algorithm within a concurrent logic programming system, VPIM, has been evaluated and the results, for a wide selection of benchmarks, are analyzed here. The authors show 1) how much the algorithm reduces the contention for critical sections during garbage collection, 2) how well the load-balancing strategy works and its expected overheads, and 3) the expected speedup achieved by the algorithm.< >